Economic and Financial Reform in El Salvador: Challenges and Opportunities to 2025 - Sohn, Ira (Journal of Applied Business and Economics, 2019)
This paper reviews El Salvador’s vital statistics and recent economic and political events that impact the economy. El Salvador -- Central America’s most densely populated though smallest country in land area -- has one of the highest homicide rates in the world in one of the world’s most violent regions. Vulnerable to extreme weather-related events and external economic shocks such as the volatility in international oil prices, the country faces major challenges because of its appalling levels of crime, violence, and corruption. Using a framework that assesses the performance of a national economy that participates in today’s globalized world, I identify the strengths and weaknesses of El Salvador’s economy towards the end of enhancing the future performance of its economy.